The 5 love languages of teenagers : the secret to loving teens effectively - Chapman, Gary D., 1938- (Chicago : Northfield Publishing, 2016)
"Socially, mentally, and spiritually, teenagers face a variety of pressures and stresses each day. Despite these pressures, it is still parents who can influence teens the most, and The 5 Love Languages of Teenagers equips parents to make the most of that opportunity. In this adaptation of the [original bestseller The 5 Love Languages], Dr. Gary Chapman explores the world in which teenagers live, explains their developmental changes, and gives tools to help you identify and appropriately communicate in your teen's love language. Get practical tips for how to: express love to your teen effectively; navigate the key issues in your teen's life, including anger and independence; set boundaries that are enforced with discipline and consequences; support and love your teen when he or she fails. Get ready to discover how the principles of the five love languages can really work in the life of your teenager and family."--Publisher's website.
Understanding today's teenagers -- The key: love from parents -- Love language #1: words of affirmation -- Love language #2: physical touch -- Love language #3: quality time -- Love language #4: acts of service -- Love language #5: gifts -- Discover your teenager's primary love language -- Anger and teenagers -- Loving your teen in single-parent and blended families -- Love and the desire for independence -- Love and the need for responsibility -- Loving when your teen fails.
Includes bibliographical references.
Keywords: Adolescent psychology; Parent and child; Love